IGR J18293−1213 is an eclipsing cataclysmic variable. Issue 1 (7th June 2016) - Clavel, M.; Tomsick, J. A.; Bodaghee, A.; Chiu, J.-L.; Fornasini, F. M.; Hong, J.; Krivonos, R.; Ponti, G.; Rahoui, F.; Stern, D.
Abstract: Studying the population of faint hard X-ray sources along the plane of the Galaxy is challenging because of high extinction and crowding, which make the identification of individual sources more difficult. IGR J18293−1213 is part of the population of persistent sources which have been discovered by the INTEGRAL satellite. We report on NuSTAR and Swift /XRT observations of this source, performed on 2015 September 11. We detected three eclipsing intervals in the NuSTAR light curve, allowing us to constrain the duration of these eclipses, Δ t= 30.8^+6.3_-0.0 min, and the orbital period of the system, T = 6.92 ± 0.01 h. Even though we only report an upper limit on the amplitude of a putative spin modulation, the orbital period and the hard thermal bremsstrahlung spectrum of IGR J18293−1213 provide strong evidence that this source is a magnetic cataclysmic variable. Our NuSTAR and Swift /XRT joint spectral analysis places strong constraints on the white dwarf mass M_wd = 0.78^+0.10_-0.09 M⊙ . Assuming that the mass to radius ratio of the companion star M ⋆ / R ⋆ = 1 (solar units) and using T, Δ t, and M wd, we derived the mass of the companion star M ⋆ = 0.82 ± 0.01 M⊙, the orbital separation of the binary system a = 2.14 ± 0.04 R⊙, and its orbital inclination compared to the line of sight i=(72 ^°_. 2^+2.4_-0.0)± 1 ^°_. 0 .